Clinical profile of pythium keratitis: perioperative measures to reduce risk of recurrence. Issue 2 (13th September 2017) - Agarwal, Shweta; Iyer, Geetha; Srinivasan, Bhaskar; Agarwal, Mamta; Panchalam Sampath Kumar, Shobha; Therese, Lily K
Abstract : Purpose: To report the clinical profile and role of perioperative adjunctive measures to reduce the risk of recurrence in Pythium insidiosum keratitis. Methods: Retrospective analysis of 10 eyes of 10 patients with P. insidiosum keratitis. Diagnosis was confirmed by PCR DNA sequencing. Results: 7out of 10 patients were from urban locales, and none had any obvious history of injury with vegetative matter and were being treated for fungal keratitis. 6 eyes presented with central full thickness infiltrates with subepithelial and superficial stromal infiltrates radiating in a reticular pattern. Corneal scraping in all eyes revealed sparsely septate fungal-like filaments on potassium hydroxide/Calcofluor. All eyes underwent the first therapeutic penetrating keratoplasty (TPK) based on worsening or non-responsiveness of clinical features to the antifungal regimen. Recurrence was noted in 7 out of 10 eyes of which 2 eyes underwent evisceration. Of the six eyes that underwent cryotherapy following confirmation of microbiological diagnosis of Pythium (along with primary TPK-1, with re-TPK-5), only one eye had a recurrence and had to be eviscerated. Of the two eyes that did not undergo cryotherapy during re-TPK, following microbiological diagnosis, one eye had a recurrence and had to be eviscerated. In two eyes with adjoining scleritis, the host bed was swabbed using absolute alcohol of which one eye was salvaged. Conclusion: This series highlights the need to be aware of this entity in the management of refractory fungal keratitis. It also brings to fore the adjunctive measures that could have a beneficial role in the management of pythium keratitis.